Implementasi Permainan Tradisional Gobak Sodor Untuk Meningkatkan Sikap Gotong Royong dan Kolaborasi Siswa Kelas IV di SD Negeri Sitiharjo Kecamatan Garung Tahun Pelajaran 2023/2024 - Usykiroh, Wiwied Nurina; Khoiri , Akhmad; Sugiyanto , Bambang (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research aims: 1) to determine the implementation of the traditional game gobak sodor in class IV of Sitiharjo State Elementary School for the 2023/2024 academic year; 2) to determine the increase in the attitude of mutual cooperation and collaboration in class IV students at Sitiharjo State Elementary School for the 2023/2024 academic year after implementing the traditional game gobak sodor; 3) to find out whether there are differences in the mutual cooperation and collaboration attitudes of fourth grade students at Sitiharjo State Elementary School for the 2023/2024 academic year who apply the traditional game gobak sodor and those who do not. This research uses a quantitative approach, a type of truei-experimental design research with a posttest-only control group method. The sample in the research was class IV of Sitiharjo State Elementary School, Garung District, which consisted of two classes, namely IVA as the experimental class and IVB as the control class. Data collection techniques in research are in the form of observation, posttest questionnaires. The posttest in the form of a questionnaire was tested using validity and reliability tests. Data analysis in research uses normality, homogeneity and t-test tests. The results of the research show that: 1) the implementation of the traditional game Gobak Sodor was successfully implemented well, as shown by a score of 75%. This value includes teacher and student activities, showing that the application of the traditional game Gobak Sodor in learning is active and effective, 2) there is an increase in students' mutual cooperation and collaboration after the implementation of the traditional game Gobak Sodor. This is proven by the results of the questionnaire in the experimental class being higher than the control class, namely the score for the mutual cooperation questionnaire was 93.5 > 66.5 while the score for collaboration was 91 > 73.45. 3) the application of the traditional game gobak sodor has proven effective in increasing attitudes of mutual cooperation and collaboration. This is proven by the results of statistical analysis obtained by Sig value data. for mutual cooperation is This is proven by the results of the t test which obtained a Sig value. for mutual cooperation, namely 0.000 < 0.05 and the Sig value. namely 0.003 < 0.05 for collaboration, it can be concluded that Ho is rejected and Ha is accepted, indicating that there is a significant difference in the level of students' sustainable awareness between the experimental class and the control class.